2015
DOI: 10.1016/j.abb.2014.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Independent evolution of four heme peroxidase superfamilies

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
178
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(204 citation statements)
references
References 65 publications
5
178
0
1
Order By: Relevance
“…We also demonstrated that the availability of a HS ligand can compensate this instability and render the enzyme properties wild-type-like. Since the overall subunit fold of proteins within the peroxidaseCld family (structural CDE superfamily) is highly conserved [1,2,60] and Cld-like proteins (HemQs) and Clds share similar active site architecture, our study has provided a better insight into the biochemistry of Cld-like proteins. The most striking difference between Cld-like proteins, HemQs, and functional Clds is the catalytic distal arginine which is fully conserved only in the latter.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also demonstrated that the availability of a HS ligand can compensate this instability and render the enzyme properties wild-type-like. Since the overall subunit fold of proteins within the peroxidaseCld family (structural CDE superfamily) is highly conserved [1,2,60] and Cld-like proteins (HemQs) and Clds share similar active site architecture, our study has provided a better insight into the biochemistry of Cld-like proteins. The most striking difference between Cld-like proteins, HemQs, and functional Clds is the catalytic distal arginine which is fully conserved only in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Mutational studies on Clds from 'Candidatus Nitrospira defluvii' (NdCld) [12,23] and from D. aromatica (DaCld) [24] revealed that the distal arginine -the only charged residue on the distal side of the haeme -is very important for chlorite degradation. It is conserved in Clds and DyPs, whereas in HemQs alanine, leucine, glutamine or serine can be found at this position ( Figure 1A) [1,11,12]. HemQs do not show any chlorite degrading activity [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 They play a key role in lignin degradation enabling the fungal decay of wood and other lignocellulosic biomass for carbon recycling in land ecosystems. 2,3 Enzymatic delignification and lignin modification are of high biotechnological interest, having multiple potential applications from paper pulp manufacturing to the production of biofuels, chemicals and added value products in lignocellulose biorefineries, where all biomass constituents should be used.…”
Section: Introductionmentioning
confidence: 99%